THE ROLE OF THE REGIONAL DEVELOPMENT AGENCY IN THE ECONOMIC DEVELOPMENT - Elfadhli, Elfadhli; Budiman, Fajar; Bonavido, Nabil (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The purpose of this research is to find out the role of the Regional Planning, Research and Development Agency (BARENLITBANGDA) as a planner in the economic development of Sawahlunto City. The type of research conducted is field research or field research with a descriptive qualitative approach. Data collection techniques that the authors use are interviews and documentation. The analysis technique used is data reduction, data presentation, and drawing conclusions. The results showed that BARENLITBANGDA of Sawahlunto City as a planning agency in the economic development of Sawahlunto City has a major role, namely planning economic development in Sawahlunto City. The economic development plan that had been prepared by BARENLITBANGDA for Sawahlunto City was submitted to the Mayor and discussed at the Sawahlunto City RPJMD meeting involving all parties related to economic development in Sawahlunto City. Benefits of research For the author to know more deeply about the role of BARENLITBANGDA in the economic development of Sawahlunto City.Keywords: Role, Obstacle, BARENLITBANGDA